The Lousy Adult - Cobb, William J. (William James), 1957- (Book collections on Project MUSE., 2013)
In The Lousy Adult, William J. Cobb reveals a world where love and respect collide with achievement and desire, a world where people often get what they want, yet must pay the price of alienation, remorse, and retribution in order to obtain it. In "The Sea Horse," a teenage boy defends a battered woman against her abusive husband while he deals with the loss of his own parents. In "Warsaw, 1984," a young man travels through Europe and ends up in a relationship in a country he can't understand. The Lousy Adult presents ten short stories about defrocked priests, guilty electricians, hardened mothers, and other colorful characters who portray the complexity of the human race. Praise for William J. Cobb's The Fire Eaters "Cobb's short stories, printed in the New Yorker and other magazines, hinted at the power he displays in this beautifully controlled and convincing debut, winner of the 1992 Associated Writing Programs award for the novel."? Publisher's Weekly.